PEMBERDAYAAN MASYARAKAT BERBASIS “POSYANDU SAHABAT MASYARAKAT” DALAM UPAYA PENANGGULANGAN STIGMA TB DI KELURAHAN SINDUMARTANI, KAPANEWON NGEMPLAK, KAB. SLEMAN, D.I. YOGYAKARTA - Wittin Khairani,; Sri Haryanti,; Haryono, Haryono (JURNAL PENGABDIAN MANDIRI, 2025)
Stigma factor is one of the obstacles to solving TB Problems in Indonesia in from environment. Stigma in TB patient is to ostracize TB patients so that treatment is not completed in TB patients. In Indonesia, the death rate from TB disease ranks 3 rd from other chronic diseases. The number of TB sufferers is around 845.000 TB sufferers. Empowement is a process of public awareness that is carried out in transformative, participatory and sustainable manner through increasing the ability to handle basic problems faced and improve living conditions according to expectations. The”Community Friend Posyandu”. Approach is a revitalization of the posyandu which required the participation of local goverments and croos-sectors to the village and sub district levels. The empowerment of "Community Friend Posyandu" is carried out in the form of educational communication and forming a "TB patient care cadre" working group as an effort to pick up the ball for TB sufferers who drop out in the treatment process. Empowerment is attended by15 posyandu cadres. The implementation time of the community service activity was in October 2024. The results of this community service activity were an increase in the independence of Posyandu cadres as a PMO working group for TB patients and TB patients continued their treatment in a disciplined manner in Sindumartani Village, Ngemplak, Sleman